A Research Note on Suicidal Behavior as a Precursor to Domestic Homicide, With a Coda on Trends in Femicide Before, During and After COVID - Strang, Heather (Journal of contemporary criminal justice, 2024)
This article briefly reviews the difficulties of predicting and preventing domestic homicide. It considers the evidence on offender prior suicidal behaviour as a precursor. It includes findings from the 1950s and 1960s as well as the most recent findings on links between suicide ideation and domestic homicide intent. It also reviews ways in which these links can be further explored and operationalised to prevent future harm. It concludes with reflections on the effect of Covid on femicide trends.